2003
DOI: 10.1023/a:1023938415148
|View full text |Cite
|
Sign up to set email alerts
|

The crossroads of molecular, typological and biological species concepts: two new species of Gyrodactylus Nordmann, 1832 (Monogenea: Gyrodactylidae)

Abstract: Nucleotide sequences of nuclear ribosomal DNA internal transcribed spacers (ITS) were used to confirm morphological identification of Gyrodactylus species in Fennoscandia. Three pairs of morphologically similar or cryptic species are compared in this study. G. branchicus Malmberg, 1964 and G. rarus Wegener, 1910, hosted by the sticklebacks Gasterosteus aculeatus L. and Pungitius pungitius (L.), respectively, displayed a genetic divergence of 0.9-1.3% along 774 nucleotides of ITS (Jukes & Cantor distance). G. b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 28 publications
2
58
0
Order By: Relevance
“…Sequencing reactions were carried out on a MegaBace 1000 analysis system (GE Healthcare) using DYEnamic ET dye terminators. The PCR primers and the internal primers ITS1R (5'-ATTTGCGTTCGAGAGACCG-3'), ITS2R (5'-GGTAAT-CACGCTTGAATC-3'), ITSR3A (5'-GAGCCGAGTGATC-CACC), and ITS2F (5'-TGGTGGATCACTCGGCTCA-3') (Matějusová et al 2001, Ziętara andLumme 2003) were used for sequencing. Sequences were proofread and assembled in Vector NTI 10 (Invitrogen) and Mega 4 (Tamura et al 2007) was used to calculate genetic distances.…”
Section: Molecular Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Sequencing reactions were carried out on a MegaBace 1000 analysis system (GE Healthcare) using DYEnamic ET dye terminators. The PCR primers and the internal primers ITS1R (5'-ATTTGCGTTCGAGAGACCG-3'), ITS2R (5'-GGTAAT-CACGCTTGAATC-3'), ITSR3A (5'-GAGCCGAGTGATC-CACC), and ITS2F (5'-TGGTGGATCACTCGGCTCA-3') (Matějusová et al 2001, Ziętara andLumme 2003) were used for sequencing. Sequences were proofread and assembled in Vector NTI 10 (Invitrogen) and Mega 4 (Tamura et al 2007) was used to calculate genetic distances.…”
Section: Molecular Analysismentioning
confidence: 99%
“…These substitutions can be attributed to 24 in ITS1 (12 transitions and 12 transversions) and 18 substitutions in ITS2 (9 transitions and 9 transversions), and in addition 1 indel was found. The large number of differences (42 out of 802) observed in the ITS regions suggests that these two species are different, and although no fixed threshold exists for the separation of Gyrodactylus species, Ziętara and Lumme (2003) suggest that a 1% difference in ITS be used as a cut-off value to delineate species. The hamuli of G. ulinganisus sp.…”
Section: Commentsmentioning
confidence: 99%
“…Based on previous experience, ITS corresponds well to the morphological delineation of the Gyrodactylus species. It has even been suggested that divergence of ITS at about 1% could be used as a pragmatic indicator of conspecificity of sister species (Ziętara and Lumme 2003), because ITS sequences are nearly always homozygous, even when they differ very little between host-specific parasites living in the same environment. The lack of heterozygotes is evidence of sexual isolation (Huyse et al 2004).…”
Section: Comparison Of the Nuclear Marker Its With Mtdna Phylogenymentioning
confidence: 99%
“…The subunit 1 of the mitochondrial cytochrome oxidase (COI) gene may also be used successfully to differentiate species and local Gyrodactylus strains (Meinilä et al 2002(Meinilä et al , 2004Hansen et al 2003Hansen et al , 2007. Molecular techniques were necessary to discriminate and describe morphologically almost identical species within several Gyrodactylus groups such as G. teuchis versus G. salaris , G. jussii vs. G. macronychus and G. alexgusevi vs. G. lotae (Ziêtara and Lumme 2003), G. pictae vs. G. turnbulli (Cable et al 2005), and a number of G. rugiensis-like and G. arcuatus-like species on marine gobies (Huyse et al 2004) . Molecular discrimination of more than 70 Gyrodactylus species based on the sequences of nuclear rDNA gene cluster encompassing both spacers (ITS1 and ITS2) and 5.8S rRNA gene, proved the region suitable for species identification (Ziêtara 2004, Ziêtara and.…”
Section: Introductionmentioning
confidence: 99%